ANALISIS KARAKTERISTIK & KEBUTUHAN LAHAN PARKIR KENDARAAN DI TRANSMART CILEGON, KOTA CILEGON - Rindu Twidi Bethary; Dwi Esti Intari; Arief Budiman; Aprilia Maharani (Jurusan Teknik Sipil Universitas Bangka Belitung, 2022)
Transmart Cilegon is a modern shopping center located in Banten province. The Transmart Cilegon parking area was built as a mall parking space (off street parking). The use of available parking spaces is not always optimal, but depends on peak hours. In an effort to deal with this problem, it is necessary to provide sufficient parking space and determine the right parking model.The purpose of this study was to determine the characteristics of parking and to determine the design and need for vehicle parking spaces in the Transmart Cilegon parking area by collecting primary data through field observations and processed using Microsoft Excel. The parking characteristics at Transmart Cilegon experienced the maximum volume and the highest parking index on Saturday, February 26, 2022 with 146 cars with an index of 12.969% and 167 motorcycles with an index of 14.236%, and peaked accumulation at 16.00-16.59. The average duration for cars is 2.53 hours and motorbikes is 2.60 hours with a turnover rate of 0.802 vehicles/SRP for cars and 0.790 vehicles/SRP for motorbikes. Judging from the characteristics of the parking space, the need for available parking spaces at Transmart Cilegon is still adequate or the parking index is below 100%.